KEHIDUPAN ANAK TERLANTAR DI LKSA YUDA MANDIRI SOMBA OPU - AB, Syamsuddin (Social Welfare Study Program, 2020)
Abstract. The life of an abandoned child certainly needs protection so that he can be independent. The article aims to analyze the living conditions of neglected children who have been coached by social workers and supervisors at the Yuda Mandiri Somba Opu Child Welfare Institution. The type of research is descriptive qualitative, obtaining data from informants through in-depth interviews and observations, to analyze data by way of data reduction, data presentation and drawing conclusions. The results obtained regarding the life of street children are the pre-Karangtina situation through assessment, the availability of dormitories, in school, mental guidance and moral guidance, group and individual recitation in the afternoon. Abstrak. Kehidupan anak terlantar tentu membutuhkan perlindungan agar ia bisa mandiri. Artikel bertujuan untuk menganalisi kondisi kehidupan anak terlantar yang selama ini di bina para pekerja sosial dan pembina Lembaga Kesejahteraan Sosial Anak Yuda Mandiri Somba Opu. Adapun jenis penelitian adalah deskriptif kualitatif, perolehan data dari informan melalui wawancara mendalam maupun observasi, untuk menganalisis data dengan cara reduksi data, penyajian data dan penarikan kesimpulan. Hasil yang diperoleh tentang kehidupan anak jalanan yaitu situasi pra karantina melalui assessment, tersedianya asrama tempat tinggal, di sekolahkan, pendampingan bimbingan mental dan pembinaan akhlak, pengajian di sore hari secara berkelompok maupun individu.